SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BULU BABI (Diadema setosum) TERHADAP PERTUMBUHAN Staphylococcus aureus DI PERAIRAN DESA PELAUW - Aulia Debby Pelu; Risman Tunny; Bilkis Latuconsina (Universitas Muhamadiyah Manado, 2020)
Sea urchin (Diadema setosum) is an aquatic biota that has high nutritional value. Bioactive compounds produced by sea urchins have the potential to be used as natural antibacterial compounds. This study aims to identify chemical compounds and determine the antibacterial activity of ethanol extract of sea urchins (Diadema setosum) against the growth of Staphylococcus aureus bacteria. The research method used is the agar diffusion method. The results of phytochemical screening of sea urchin extract (Diadema setosum) showed the presence of alkaloids and saponins. By using variations in the concentration of ethanol extract of sea urchin (Diadema setosum) at a concentration of 80% it had an inhibitory power of 18 mm, a concentration of 90% had an inhibitory power of 23 mm, a concentration of 100% had an inhibitory power of 28 mm and for a concentration of 110% had an inhibitory power of 35 mm. The positive control has a resistance of 30 mm and the negative control is 0 mm. The results showed that the ethanol extract of sea urchins (Diadema setosum) had a strong bacterial inhibitory activity against Staphylococcus aureus bacteria.